High-temperature-resistant polyurethane UV (ultraviolet) light viscosity-reducing adhesive and preparation method thereof
By adopting long-chain diol and deep crosslinking network design, the problems of insufficient flexibility and peeling residues in high-temperature environments are solved, and polyurethane-type UV light-removing adhesives with high flexibility, low peeling force and no residues are achieved, which is suitable for high-temperature application scenarios.
Patent Information
- Application Number
- CN202411506984.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-10-28
AI Technical Summary
Traditional UV light-reducing adhesives have problems such as insufficient flexibility and peeling residue in high temperature environments, making it difficult to meet the performance requirements of key applications such as electronic components and automotive components.
Long-chain diols are used as the main raw material, and a deep crosslinking network is built through precise chemical synthesis and crosslinking design to improve the elasticity and impact resistance of polyurethane, and a high double bond density design is introduced through isocyanate acrylic acid to achieve low peeling force and no residue.
It significantly improves the flexibility and high elongation of break of the adhesive, ensures stable physical properties and bonding strength at high temperatures, achieves low peeling force and no residues, and is suitable for material protection in high temperature scenarios.
Smart Images

Figure CN119505788A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adhesives, and in particular relates to a high temperature resistant polyurethane type UV light viscosity reducing adhesive and a preparation method thereof. Background Art
[0002] In modern industry, the application areas of UV photosensitive adhesives are constantly expanding, especially in high temperature environments, where the demand for bonding and protecting material surfaces is growing. However, traditional UV light-sensitive adhesives often have significant problems such as insufficient flexibility and peeling residue, which makes it difficult for them to meet strict performance requirements in key applications such as electronic components and automotive parts. Therefore, the development of a new polyurethane-based UV light-sensitive adhesive with excellent flexibility, high temperature resistance and low peeling force has become a technical challenge that needs to be solved urgently. Summary of the invention
[0003] In view of the above problems, the present invention provides a high temperature resistant polyurethane type UV light viscosity reducing adhesive and a preparation method thereof, aiming to solve the deficiencies of the existing UV light viscosity reducing adhesive in terms of flexibility, high temperature resistance and peeling force. The adhesive adopts long-chain diol as the main raw material, and achieves excellent flexibility and impact resistance through precise chemical synthesis and cross-linking design. The use of the long-chain diol can effectively improve the elasticity of polyurethane, so that it can adapt to various stress conditions during the application process, thereby ensuring the overall performance stability of the material.
[0004] The purpose of the present invention is achieved by the following technical solution: A method for preparing a high temperature resistant polyurethane type UV light viscosity reducing adhesive comprises the following steps: The polyester diol or polyether polyol is subjected to high temperature dehydration and then cooled, nitrogen is introduced, isocyanate and polyurethane crosslinking agent (trimethylolpropane) are added, and the reaction is stirred for 2-3 hours; Add an organic tin catalyst and continue the reaction for 2-3 hours, then add isocyanate acrylic acid to a constant pressure dropping funnel and drip at a rate of 1 drop / s, react for 2-3 hours to form a dangling double bond, and obtain a polyurethane glue; The synthesized glue is fully stirred and mixed with anhydrous ethyl acetate solvent, a photoinitiator and an isocyanate cross-linking agent, and a tape is prepared by a roller pressing method, and a polyurethane type UV light-reducing adhesive tape is obtained after drying.
[0005] The purpose of step 1 is to react the alcohol with the crosslinker and isocyanate to form a polyurethane reaction after removing water to form a prepolymer with not too high viscosity. The purpose of step 2 is to react with the remaining hydroxyl groups to form dangling double bonds for the subsequent UV viscosity reduction process. Step 3 is to remove the solvent and make a tape.
[0006] The isocyanate acrylics mentioned above include isocyanate ethyl methacrylate (MOI) and isocyanate ethyl acrylate (AOI); The polyester diol or polyether polyol is polyethylene glycol (PEG), polypropylene glycol (PPG), polybutylene glycol (PBD), polytetramethylene glycol (PTMG), polycaprolactone (PCL), polycarbonate diol (PCDL); The isocyanate is an aliphatic isocyanate including hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), dicyclohexylmethane-4,4'-diisocyanate (HMDI), xylylene diisocyanate (XDI), and tetramethyl metaxylylene diisocyanate (TMXDI); The isocyanate crosslinking agent is an aromatic polyisocyanate (L75) based on toluene diisocyanate; The photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone (1173), phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (819), 1-hydroxy-cyclohexyl-phenyl ketone (184), 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO); The molecular weight of the polydiol is 1000-5000 g / mol. The isocyanate index R value (i.e. the molar ratio of cyanate groups to hydroxyl groups in the polydiol) used in synthesizing the prepolymer is between 0.5-0.9, and the remaining unreacted hydroxyl groups react with the isocyanate acrylate and the isocyanate crosslinking agent (the hydroxyl groups are just reacted or in excess); The present invention provides a high temperature resistant polyurethane type UV light viscosity reducing adhesive, which is prepared by the preparation method as described above. The UV light viscosity reducing adhesive comprises the following raw materials in mass fractions: 0.01-1wt% of a photoinitiator; 0.002-0.1wt% of an organic tin catalyst; and 0.25-2wt% of an isocyanate crosslinking agent.
[0007] Compared with the prior art, the high temperature resistant polyurethane UV light viscosity reducing adhesive of the present invention has the following significant advantages: Excellent flexibility: Using long-chain diols as the main raw material significantly improves the elasticity and impact resistance of the adhesive. This allows the material to better adapt to deformation when facing mechanical stress and reduce the risk of rupture.
[0008] High temperature resistance: By adding isocyanate crosslinkers to build a deep crosslinking network, the adhesive can still maintain stable physical properties and bonding strength in an environment up to 200°C. This feature far exceeds most existing UV light-reducing adhesives and is suitable for a wider range of high-temperature application scenarios.
[0009] Low peel force and no residue: The design of introducing high double bond density by adding isocyanate acrylic ensures that the adhesive has low peel force and no residue after UV irradiation, avoiding the common adhesive residue problem when peeling traditional adhesives, which is especially important for applications that need to keep the surface clean. Wide application: Combining the above properties, the polyurethane UV light-reducing adhesive prepared by the present invention has excellent flexibility and high elongation at break. The adhesive tape has low peeling strength after UV treatment, no residue after peeling, heat resistance up to 200°C, and no residual adhesive within 30 minutes. It is particularly suitable for protecting the surface of materials in high temperature scenarios, such as electronic components, automotive parts and other industrial fields, meeting higher market demands, and has important economic value and application prospects. In short, the present invention solves many deficiencies in the prior art through material optimization and innovation in preparation process, and provides a more reliable and efficient UV light-reducing adhesive. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 It is the gas chromatography-mass spectrometry (GC / MS) spectrum of the pre-UV glue in Example 1 of the present invention. DETAILED DESCRIPTION
[0011] The present invention will be further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto. Example 1
[0012] Step 1: Prepare the polyurethane glue Add 200 g of polyethylene glycol (PEG molecular weight 1000) to the reactor and remove water at 120°C for 2 hours, then cool to 60°C, introduce nitrogen, add 22 g of isophorone diisocyanate (IPDI) and 3 g of polyurethane crosslinker (trimethylolpropane), and stir to react for 2 hours; add 0.1 g of organic tin catalyst, continue to react for 3 hours, then add 8 g of isocyanate ethyl methacrylate (MOI) to the constant pressure dropping funnel, and add dropwise at a rate of 1 drop / s, and react for 2 hours.
[0013] Step 2: Prepare UV adhesive tape 100 g of the glue synthesized in step 1 was thoroughly stirred and mixed with 10 g of anhydrous ethyl acetate solvent, 0.3 g of photoinitiator 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO) and 1 g of isocyanate crosslinking agent toluene diisocyanate-based aromatic polyisocyanate (L75), and prepared into a 100 μm thick tape by a machine roller method, and dried at 120 degrees for 15 minutes to obtain a polyurethane type UV light-reducing adhesive tape.
[0014] When using, apply the adhesive to the surface to be protected (2.5cm wide and 3mm thick strips), and take three tapes for the following tests: test the peeling force before UV; heat the tape in a 200℃ oven for 30 minutes to test whether there is any residue after peeling; fully cure it with a UV curing device under 365nm LED wavelength light, and test the peeling force of the tape after UV. The results show that the peeling force of the formula before UV is 565g, no adhesive residue is left after high temperature treatment, and the peeling force after UV is 31g. Example 2
[0015] Step 1: Prepare the polyurethane glue Add 200 g of polyethylene glycol (PEG molecular weight 2000) to the reactor and remove water at 120°C for 2 hours, then cool to 60°C, introduce nitrogen, add 11 g of isophorone diisocyanate (IPDI) and 2 g of polyurethane crosslinker (trimethylolpropane), and stir to react for 2 hours; add 0.1 g of organic tin catalyst, continue to react for 3 hours, then add 5 g of isocyanate ethyl methacrylate (MOI) to the constant pressure dropping funnel, and add dropwise at a rate of 1 drop / s, and react for 2 hours.
[0016] Step 2: Prepare UV adhesive tape 100g of the glue synthesized in step 1 was fully stirred and mixed with 10g of anhydrous ethyl acetate solvent, 0.3g of photoinitiator 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO) and 1g of aromatic polyisocyanate (L75) based on isocyanate crosslinking agent toluene diisocyanate, and a 100-micron thick tape was prepared by a machine roller method, and dried at 120 degrees for 15 minutes to obtain a polyurethane type UV light-reducing adhesive tape. When in use, the adhesive was applied to the surface to be protected (2.5cm wide and 3mm thick strips), and three tapes were taken for the following tests: test the peeling force before UV; place the tape in an oven at 200℃ for 30 minutes to test whether there is residue after peeling; fully cure it with a UV curing device under 365nm LED wavelength light, and test the peeling force of the tape after UV. The results show that the peeling force of the formula before UV is 763g, there is no residual glue after high temperature treatment, and the peeling force after UV is 52g. Example 3
[0017] Step 1: Prepare the polyurethane glue Add 200 g of polyethylene glycol (PEG molecular weight 1000) to the reactor and remove water at 120°C for 2 hours, then cool to 60°C, introduce nitrogen, add 22.23 g of isophorone diisocyanate (IPDI) and 3 g of polyurethane crosslinker (trimethylolpropane), and stir to react for 2 hours; add 0.1 g of organic tin catalyst, continue to react for 3 hours, then add 10 g of isocyanate ethyl methacrylate (MOI) to the constant pressure dropping funnel, and add dropwise at a rate of 1 drop / s, and react for 2 hours.
[0018] Step 2: Prepare UV adhesive tape 100g of the glue synthesized in step 1 was fully stirred and mixed with 10g of anhydrous ethyl acetate solvent, 0.3g of photoinitiator 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO) and 1g of aromatic polyisocyanate (L75) based on isocyanate crosslinking agent toluene diisocyanate, and a 100-micron thick tape was prepared by a machine roller method, and dried at 120 degrees for 15 minutes to obtain a polyurethane UV light-reducing adhesive tape. When in use, the adhesive was applied to the surface to be protected (2.5cm wide and 3mm thick strips), and three tapes were taken for the following tests: test the peeling force before UV; place the tape in an oven at 200℃ for 30 minutes to test whether there is residue after peeling; fully cure it with a UV curing device under 365nm LED wavelength light, and test the peeling force of the tape after UV. The results show that the peeling force of the formula before UV is 615g, there is no residual glue after high temperature treatment, and the peeling force after UV is 22g. Example 4
[0019] Step 1: Prepare the polyurethane glue Add 200 g of polytetrahydrofuran (PTMG, molecular weight 1000) to the reactor and remove water at 120°C for 2 hours, then cool to 60°C, introduce nitrogen, add 22.23 g of isophorone diisocyanate (IPDI) and 3 g of polyurethane crosslinker (trimethylolpropane), and stir to react for 2 hours; add 0.1 g of organic tin catalyst, continue to react for 3 hours, then add 8 g of isocyanate ethyl methacrylate (MOI) to the constant pressure dropping funnel, and add dropwise at a rate of 1 drop / s, and react for 2 hours.
[0020] Step 2: Prepare UV adhesive tape 100g of the glue synthesized in step 1 was fully stirred and mixed with 10g of anhydrous ethyl acetate solvent, 0.3g of photoinitiator 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO) and 1g of aromatic polyisocyanate (L75) based on isocyanate crosslinking agent toluene diisocyanate, and a 100-micron thick tape was prepared by a machine roller method, and dried at 120 degrees for 15 minutes to obtain a polyurethane UV light-reducing adhesive tape. When in use, the adhesive was applied to the surface to be protected (2.5cm wide and 3mm thick strips), and three tapes were taken for the following tests: test the peeling force before UV; heat the tape in an oven at 200℃ for 30 minutes to test whether there is residue after peeling; fully cure it with a UV curing device under 365nm LED wavelength light, and test the peeling force of the tape after UV. The results show that the peeling force of the formula before UV is 445g, there is no residual glue after high temperature treatment, and the peeling force after UV is 26g. Example 5
[0021] Step 1: Prepare the polyurethane glue Add 200 g of polytetrahydrofuran (PTMG, molecular weight 1000) to the reactor, remove water at 120°C for 2 hours, cool to 60°C, introduce nitrogen, add 22.23 g of dicyclohexylmethane-4,4'-diisocyanate (HMDI) and 8 g of polyurethane crosslinker (trimethylolpropane), stir and react for 2 hours; add 0.1 g of organic tin catalyst, continue to react for 3 hours, then add 15 g of isocyanate ethyl methacrylate (MOI) to the constant pressure dropping funnel, and add it dropwise at a rate of 1 drop / s, and react for 2 hours.
[0022] Step 2: Prepare UV adhesive tape 100g of the glue synthesized in step 1 was fully stirred and mixed with 10g of anhydrous ethyl acetate solvent, 0.3g of photoinitiator 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO) and 1g of aromatic polyisocyanate (L75) based on isocyanate crosslinking agent toluene diisocyanate, and a 100-micron thick tape was prepared by a machine roller method, and dried at 120 degrees for 15 minutes to obtain a polyurethane UV light-reducing adhesive tape. When in use, the adhesive was applied to the surface to be protected (2.5cm wide and 3mm thick strips), and three tapes were taken for the following tests: test the peeling force before UV; place the tape in an oven at 200℃ for 30 minutes to test whether there is residue after peeling; fully cure it with a UV curing device under 365nm LED wavelength light, and test the peeling force of the tape after UV. The results show that the peeling force of the formula before UV is 1565g, the residual glue is treated at high temperature, and the peeling force after UV is 82g. Example 6
[0023] Step 1: Prepare the polyurethane glue Add 200 g of polyethylene glycol (PEG molecular weight 3000) to the reactor and remove water at 120°C for 2 hours, then cool to 60°C, introduce nitrogen, add 5 g of isophorone diisocyanate (IPDI) and 1 g of polyurethane crosslinker (trimethylolpropane), and stir to react for 2 hours; add 0.1 g of organic tin catalyst, continue to react for 3 hours, then add 2 g of isocyanate ethyl acrylate (AOI) to the constant pressure dropping funnel, and add dropwise at a rate of 1 drop / s, and react for 2 hours.
[0024] Step 2: Prepare UV adhesive tape 100g of the glue synthesized in step 1 was fully stirred and mixed with 10g of anhydrous ethyl acetate solvent, 0.3g of photoinitiator 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO) and 1g of aromatic polyisocyanate (L75) based on isocyanate crosslinking agent toluene diisocyanate, and a 100-micron thick tape was prepared by a machine roller method, and dried at 120 degrees for 15 minutes to obtain a polyurethane type UV light-reducing adhesive tape. When in use, the adhesive was applied to the surface to be protected (2.5cm wide and 3mm thick strips), and three tapes were taken for the following tests: test the peeling force before UV; place the tape in an oven at 200℃ for 30 minutes to test whether there is residue after peeling; fully cure it with a UV curing device under 365nm LED wavelength light, and test the peeling force of the tape after UV. The results show that the peeling force of the formula before UV is 911g, there is slight residual glue after high temperature treatment, and the peeling force after UV is 132g.
[0025] Examples 1, 3, and 4 are cases with better effects. Due to different raw materials and ratios, the corresponding tape performance varies according to different application scenarios. Example 5: Due to excessive amounts of polyurethane cross-linking agent, there are not enough residual hydroxyl groups in the glue. The isocyanate cross-linking agent does not work during the subsequent high-temperature preparation of the tape, resulting in high-temperature residual glue. Example 6: The molecular weight of polyethylene glycol is too large, the product cross-linking density is not enough, the reaction is not sufficient, and slight residual glue is generated. The gas chromatography-mass spectrometry (GC / MS) spectrum of the pre-UV glue in Example 1 is shown in the figure. Figure 1 As shown, the key structures such as polyurethane components and unsaturated double bond components that may be contained in the glue are shown above. Comparative Example 1
[0026] Step 1: Prepare the polyurethane glue Add 200 g of polyethylene glycol (PEG molecular weight 1000) to the reactor and remove water at 120°C for 2 hours, then cool to 60°C, introduce nitrogen, add 22.23 g of isophorone diisocyanate (IPDI) and 3 g of polyurethane crosslinker (trimethylolpropane), and stir to react for 2 hours; add 0.1 g of organic tin catalyst, continue to react for 3 hours, then add 1 g of isocyanate ethyl methacrylate (MOI) to the constant pressure dropping funnel, and add dropwise at a rate of 1 drop / s, and react for 2 hours.
[0027] Step 2: Prepare UV adhesive tape 100g of the glue synthesized in step 1 was fully stirred and mixed with 10g of anhydrous ethyl acetate solvent, 0.3g of photoinitiator 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO) and 1g of aromatic polyisocyanate (L75) based on isocyanate crosslinking agent toluene diisocyanate, and a 100-micron thick tape was prepared by a machine roller method, and dried at 120 degrees for 15 minutes to obtain a polyurethane UV light-reducing adhesive tape. When in use, the adhesive was applied to the surface to be protected (2.5cm wide and 3mm thick strips), and three tapes were taken for the following tests: test the peeling force before UV; place the tape in an oven at 200℃ for 30 minutes to test whether there is residue after peeling; fully cure it with a UV curing device under 365nm LED wavelength light, and test the peeling force of the tape after UV. The results show that the peeling force of the formula before UV is 665g, there is no residual glue after high temperature treatment, and the peeling force after UV is 318g. Comparative Example 2
[0028] Step 1: Prepare the polyurethane glue Add 200 g of polyethylene glycol (PEG molecular weight 1000) to the reactor and remove water at 120°C for 2 hours, then cool to 60°C, introduce nitrogen, add 22.23 g of isophorone diisocyanate (IPDI) and 3 g of polyurethane crosslinker (trimethylolpropane), and stir to react for 2 hours; add 0.1 g of organic tin catalyst, continue to react for 3 hours, then add 8 g of isocyanate ethyl methacrylate (MOI) to the constant pressure dropping funnel, and add dropwise at a rate of 1 drop / s, and react for 2 hours.
[0029] Step 2: Prepare UV adhesive tape 100g of the glue synthesized in step 1 was fully stirred and mixed with 10g of anhydrous ethyl acetate solvent, 0.3g of photoinitiator 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO) and 0.1g of aromatic polyisocyanate (L75) based on isocyanate crosslinking agent toluene diisocyanate, and a 100-micron thick tape was prepared by a machine roller method, and then dried at 120 degrees for 15 minutes to obtain a polyurethane UV light-reducing adhesive tape. When in use, the adhesive was applied to the surface to be protected (a 2.5cm wide and 3mm thick strip), and three tapes were taken for the following tests: test the peeling force before UV; place the tape in an oven at 200℃ for 30 minutes to test whether there is any residue after peeling; fully cure it with a UV curing device under 365nm LED wavelength light, and test the peeling force of the tape after UV. The results showed that the peeling force of the formula before UV was 561g, and the residual glue was treated at high temperature, and the peeling force after UV was 52g. Comparative Example 3
[0030] Step 1: Prepare the polyurethane glue Add 200 g of polyethylene glycol (PEG molecular weight 1000) to the reactor and remove water at 120°C for 2 hours, then cool to 60°C, introduce nitrogen, add 22.23 g of isophorone diisocyanate (IPDI) and 3 g of polyurethane crosslinker (trimethylolpropane), and stir to react for 2 hours; add 0.1 g of organic tin catalyst, continue to react for 3 hours, then add 8 g of isocyanate ethyl methacrylate (MOI) to the constant pressure dropping funnel, and add dropwise at a rate of 1 drop / s, and react for 2 hours.
[0031] Step 2: Prepare UV adhesive tape 100g of the glue synthesized in step 1 was fully stirred and mixed with 10g of anhydrous ethyl acetate solvent, 0.01g of photoinitiator 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO) and 1g of aromatic polyisocyanate (L75) based on isocyanate crosslinking agent toluene diisocyanate, and a 100-micron thick tape was prepared by a machine roller method, and dried at 120 degrees for 15 minutes to obtain a polyurethane type UV light-reducing adhesive tape. When in use, the adhesive was applied to the surface to be protected (2.5cm wide and 3mm thick strips), and three tapes were taken for the following tests: test the peeling force before UV; heat the tape in an oven at 200℃ for 30 minutes to test whether there is residue after peeling; fully cure it with a UV curing device under 365nm LED wavelength light, and test the peeling force of the tape after UV. The results show that the peeling force of the formula before UV is 575g, there is no residual glue after high temperature treatment, and the peeling force after UV is 422g.
[0032] Compared with Example 1, Comparative Example 1 reduces the amount of isocyanate ethyl methacrylate (MOI), resulting in insufficient crosslinking density, poor viscosity reduction effect, and a significant increase in post-UV peeling force; Compared with Example 1, Comparative Example 2 reduces the amount of isocyanate crosslinker L75, resulting in insufficient crosslinking during thermal curing and residual glue after high-temperature treatment; Compared with Example 1, Comparative Example 3 reduces the amount of photoinitiator TPO, resulting in insufficient photocuring during the UV treatment process and a significant increase in post-UV peeling force.
[0033] Table 1 Performance test results of high temperature resistant polyurethane UV light de-viscosity adhesives of different embodiments and comparative examples
[0034] The high temperature resistant polyurethane type UV light viscosity reducing adhesive provided by the present invention adopts long-chain diols as the main raw material. This long-chain structure not only enhances the flexibility of the material, but also gives the adhesive better impact resistance, so that it can effectively absorb and disperse the influence of force when subjected to external stress, thereby maintaining good deformation characteristics. In addition, the preparation process of the adhesive significantly improves its high temperature resistance through the construction of a cross-linked network (addition of a cross-linking agent), so that the product can still maintain excellent physical properties and bonding strength at temperatures up to 200°C. This deep cross-linked structure not only improves the thermal stability of the adhesive, but also effectively prevents the performance from degrading at high temperatures. After UV light irradiation, the high double bond density structure formed by the adhesive is the key to achieving low peeling force. The high double bond density significantly reduces the peeling strength of the material after UV, ensuring that there is no residue during the peeling process. This feature is particularly important for applications that require clean surfaces, such as protective films for electronic components and automotive coatings. In summary, the development of this polyurethane UV light-resistant viscosity-reducing adhesive not only meets the needs of high-temperature application scenarios, but also has significant market application potential and economic value, heralding technological innovation and industrial development in related fields.
[0035] The above description is only part of the embodiments of the present invention and is not intended to limit the present invention. All equivalent changes and modifications made according to the content of the present invention are within the protection scope of the present invention.
Claims
1. A method for preparing a high temperature resistant polyurethane UV light viscosity reducing adhesive, characterized in that: The following steps are involved: a. The polyester diol or polyether polyol is subjected to high temperature dehydration and then cooled, nitrogen is introduced, isocyanate and polyurethane crosslinker are added, and the reaction is stirred for 2-3 hours; b. Add an organic tin catalyst, continue the reaction for 2-3 hours, then add isocyanate acrylic acid to a constant pressure dropping funnel, and drip at a certain rate, react for 2-3 hours to obtain a polyurethane glue; c. The synthesized glue was fully stirred and mixed with anhydrous ethyl acetate solvent, a photoinitiator and an isocyanate crosslinking agent, and a tape was prepared by a roller pressing method, and a polyurethane type UV light-reducing adhesive tape was obtained after drying.
2. The method for preparing a high temperature resistant polyurethane type UV light viscosity reducing adhesive according to claim 1, characterized in that: The isocyanate acrylate includes isocyanate ethyl methacrylate and isocyanate ethyl acrylate.
3. The method for preparing a high temperature resistant polyurethane type UV light viscosity reducing adhesive according to claim 1, characterized in that: The polyester diol or polyether polyol is polyethylene glycol, polypropylene glycol, polybutylene glycol, polytetrahydrofuran, polycaprolactone, or polycarbonate diol.
4. The method for preparing a high temperature resistant polyurethane type UV light viscosity reducing adhesive according to claim 1, characterized in that: The isocyanate is an aliphatic isocyanate including hexamethylene diisocyanate, isophorone diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, xylylene diisocyanate, and tetramethyl-meta-xylylene diisocyanate.
5. The method for preparing a high temperature resistant polyurethane type UV light viscosity reducing adhesive according to claim 1, characterized in that: The isocyanate crosslinking agent is an aromatic polyisocyanate based on toluene diisocyanate.
6. The method for preparing a high temperature resistant polyurethane UV light viscosity reducing adhesive according to claim 1, characterized in that: The photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone, phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide, 1-hydroxy-cyclohexyl-phenyl ketone, and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.
7. The method for preparing a high temperature resistant polyurethane type UV light viscosity reducing adhesive according to claim 1, characterized in that: The polyurethane crosslinking agent is trimethylolpropane; and the organic tin catalyst is dibutyltin dilaurate catalyst.
8. The method for preparing a high temperature resistant polyurethane type UV light viscosity reducing adhesive according to claim 1, characterized in that: The molecular weight of the polyester diol is 1000-5000; the isocyanate index R value (i.e. the molar ratio of cyanate groups to hydroxyl groups in polyester diol or polyether polyol) used in synthesizing the prepolymer is between 0.5-0.9, and the remaining unreacted hydroxyl groups react with isocyanate acrylate and isocyanate crosslinking agent.
9. A high temperature resistant polyurethane UV light viscosity reducing adhesive, characterized in that: The UV light viscosity-reducing adhesive is prepared by the preparation method according to any one of claims 1 to 8, wherein the UV light viscosity-reducing adhesive comprises the following raw materials in mass fractions: 0.01-1wt% of a photoinitiator; 0.002-0.1wt% of an organic tin catalyst; and 0.25-2wt% of an isocyanate crosslinking agent.
Citation Information
Patent Citations
Adhesive composition, UV viscosity-reducing adhesive tape and preparation method thereof
CN114517069A
High-temperature-resistant, high-flexibility and high-hardness polyurethane acrylate and preparation thereof
CN115584008A
Michael Acceptor Comprising Multiple Hydroxyl Group, And Michael Addition Comprising Derived The Same.
KR1020110112981A
Urethane (METH)acrylate composition
WO2013099766A1
Improved tack-free properties of light-curable compositions
WO2024050272A1
Cited By
Thermal viscosity-reducing adhesive, preparation method thereof and thermal viscosity-reducing adhesive product
CN120248795A